Clinical and pathological differences between skin‐limited IgM/IgG vasculitis and skin‐limited IgA vasculitis - Miho Kawamura; Yuki Mizutani; Yoko Mizutani; Kanako Matsuyama; En Shu; Tatsuhiko Miyazaki; Mariko Seishima (Frontiers Media S.A., 2021)
Abstract Objectives Cutaneous IgM/IgG vasculitis (IgM/IgG V) is characterized by leukocytoclastic vasculitis histologically and by IgM‐ or IgG‐ perivascular deposition. However, clinical differences between IgM/IgG V and skin‐limited IgA vasculitis (IgA V) have not been fully clarified. In the present study, we assessed the clinical and histopathological differences between IgM/IgG V and IgA V. Methods We examined 14 patients with IgM/IgG V and 24 patients with skin‐limited IgA V. The cases associated with systemic diseases were excluded. Clinical findings, laboratory data, and histological findings were compared between IgM/IgG V and IgA V groups. Results Livedo lesions appeared more often, and palpable purpura less often in IgM/IgG V. Localization of the lesions was more limited to the lower legs in IgM/IgG V. In laboratory data, there were no statistical differences in peripheral blood cell counts, IgG, IgA, and IgM levels between the two groups. Histopathological findings showed less infiltration of neutrophils, CD8+ T cells, and CD3+ T cells, and nuclear dusts in IgM/IgG V. Systemic steroids were administered significantly less frequently in IgM/IgG V cases, but the recurrence rate did not differ. Conclusions Based on these results, IgM/IgG V may be a clinically and histologically different entity from IgA V. However, further studies are necessary to define the differences between them more clearly.